SISTEM PAKAR BERBASIS WEB DIAGNOSA JENIS PENYAKIT PADA LAMBUNG MANUSIA - Mukhlis Yuliansyah (Telematika, 2013)
One of the issues touched by the expert system is diagnostic in the field of health, theinitial suspicion to diagnose diseases in the human stomach. Gastric disease or disorder can beinfected by the disease so that the public needs to be aware. Therefore, the dissemination ofinformation about the disease is needed to find out more types of the disease early. Types ofgastric disease is Irritable Bowel Syndrome, Acute Superficial Gastritis, Chronic atrophicgastritis, peptic ulcer, Gastroesophageal Reflux (GERD), Functional Dyspepsia, GasterMalignant Tumors, Ulcers Gaster. Thus aims to generate web-based expert systems inmedicine to diagnose diseases in human gastric symptoms through perceived user. Themethodology used for the research of expert system development methods. Methods to build anexpert system that Forward Chaining method to search Depth First Search. References fromthe internet, books and people skilled in the art that dr.Susilaningsih, who worked at theHospital PKU Muhmammadiyah Yogyakarta. As for the software using PHP as theprogramming language and MySQL as database.Keyword : Expert System, Disease in The Human Stomach, WEB, Forward Chaining